Mingmu Xiaoyao granules regulate the PI3K/Akt/mTOR signaling pathway to reduce anxiety and depression and reverse retinal abnormalities in rats - Ma, Qiuyan; Zhou, Jian; Yang, Ziyi; Xue, Yuxin; Xie, Xinran; Li, Tiejun; Yang, Yingxin (Frontiers in Pharmacology, 2022)
Objective: To investigate the effects of Mingmu Xiaoyao granules (MMXY) on the morphology and function of the retina and the mechanism of PI3K/Akt/mTOR pathway-related proteins in rats with anxiety and depression induced by chronic unpredictable mild stress (CUMS). Methods: Fifty-two male Sprague Dawley rats were randomly allocated to either a control (n=14) or a simulated CUMS group (n=38). The CUMS model was established successfully at 4 weeks. Six rats in each group were randomly selected to be sacrificed and their retinas isolated for histological examination. At 5 weeks, rats in the CUMS group were randomly allocated to the following groups: Model (CUMS+ pure water), MMXY-H (CUMS+MMXY 7.2 g/Kg/d), MMXY-L (CUMS+MMXY 3.6 g/Kg/d), and CBZ (CUMS+ Carbamazepine 20 mg/Kg/d), with eight rats in each group. All rats were given the relevant intervention once a day. At 12 weeks, sucrose preference and open field tests were performed to evaluate the anxiety and depression status of rats. In live rats, optical coherence tomography angiography was used to measure retinal thickness and blood flow, while electroretinograms (ERGs) and visual evoked potentials (VEPs) were used to evaluate retinal function. The next day, the specimens were sacrificed for serological, histological, immunofluorescence, Western blot and transmission electron microscopy examinations to explore the mechanism of MMXY in CUMS rats. Results: MMXY improved the anxiety and depression-like behavior of rats. Results of optical coherence tomography angiography showed that MMXY improved retinal inner thickness and blood flow in CUMS rats. MMXY improved the amplitude of a- and b-waves in the scotopic and photopic ERG, as well as N2 and P2 peak time and amplitude in the flash-VEP in CUMS rats. Retinal histological staining and transmission electron microscopy showed that MMXY reversed retinal morphology and ultrastructure in CUMS rats. MMXY reduced the expression of Beclin1 and LC3I/II proteins, regulated the PI3K/Akt/mTOR pathway, inhibited autophagy, and had a protective effect on the retina in CUMS rats. Conclusions: MMXY may effectively improve retinal morphology and function as well as anxiety and depression-like behaviors in CUMS rats by regulating the PI3K/Akt/mTOR signaling pathway.